2011
DOI: 10.1159/000335803
|View full text |Cite
|
Sign up to set email alerts
|

The Antiapoptotic Effects of Sulphurous Mineral Water and Sodium Hydrosulphide on Diabetic Rat Testes

Abstract: Background/Aims: It is well known that diabetes mellitus is associated with the impairment of testicular function. In the present study, we aimed to study the effects of sulphurous mineral water or sodium hydrosulphide (NaHS) on apoptotic testicular damage in rats with streptozotocin (STZ)-induced diabetes. Methods: Sulphurous mineral water (as drinking water) or NaHS (14 µmol/kg body weight/day, I.P.) was administered for 7 wks to rats with STZ-induced diabetes. Results: Hyperglycaemia, an overproduction of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
0
12
0
1
Order By: Relevance
“…This was accompanied by increased testicular oxidative stress markers, as decreased level of GSH and increased lipid peroxidation content, as well as by increased expression of the apoptotic marker; caspase 3. Previous studies have shown that several compounds possessing antioxidant properties might confer testicular protection against diabetes-induced oxidative stress and/or apoptotic markers, as sulfurous mineral water and sodium hydrosulfide,[17] curcumin,[18] quercetin,[19] ferulic acid,[20] pioglitazone,[21] and melatonin. [22]…”
Section: Discussionmentioning
confidence: 99%
“…This was accompanied by increased testicular oxidative stress markers, as decreased level of GSH and increased lipid peroxidation content, as well as by increased expression of the apoptotic marker; caspase 3. Previous studies have shown that several compounds possessing antioxidant properties might confer testicular protection against diabetes-induced oxidative stress and/or apoptotic markers, as sulfurous mineral water and sodium hydrosulfide,[17] curcumin,[18] quercetin,[19] ferulic acid,[20] pioglitazone,[21] and melatonin. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Another study pointed to increasing seminiferous tubule wall thickness, germ cell depletion, and Sertoli cell vacuolization in diabetic human testicular biopsies (8) and in diabetic rats (9).…”
Section: Introductionmentioning
confidence: 97%
“…Experimental studies suggested that testicular and erectile dysfunction and spermatogenic disruption in the testis were responsible for the observed low testosterone levels in experimental diabetic animals (9). Control of apoptosis is essential for healthy spermatogenesis in the adult testes (10).…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis is highly complex and critical process for maintaining male fertility. The continuous self-renewal and differentiation of spermatogonial stem cells (SSC) is the most important step for maintaining sperm production, and this process involves numerous molecules and pathways [10,11].…”
Section: Introductionmentioning
confidence: 99%